Spontaneous subarachnoid hemorrhage in a referral health Centre in Central Africa - Daniel Gams Massi; Mikael Doufiene Pazeu; Mathieu Motah; Annick Melanie Magnerou; Caroline Kenmegne; Salomon Mbahé; Njankouo Yacouba Mapoure (eNeurologicalSci)
Background: Spontaneous subarachnoid hemorrhage (sSAH) is a medicosurgical emergency with high morbidity and mortality. The aimed of this study was to describe the clinical features and outcome of sSAH in Cameroon. Methods: We reviewed medical records of patients aged ≥15 years old, admitted for sSAH from Januray 2011 to December 2020 in the Douala General Hospital. The diagnosis of sSAH was confirmed by neuroimaging (CT scan or MRI). Clinical and radiological severities were assessed by the WFNS score and the modified Fisher score respectively. Factors associated to in-hospital mortality was identified using cross-table (RR and 95%CI). Results: Among the 111 cases of sSAH reviewed in emergencies records, we included 70 patients. The mean age was of 55.6 ± 13.6 years. Female were predominant (57.1%). Altered consciousness was the main clinical feature (55.7%). The WFNS score was grade 4–5 in 54.3% of patients. And 75.7% of cases presented a modified Fisher score of 3–4. Ruptured of intracranial aneurysm was the most common etiology (46.2%). Endovascular treatment and/or surgical treatment were not avaible. Hospital-based mortality was 40% and factor associated with death were Altered consciousness (RR: 4.3, 95%CI:1.52–12.33, p = 0.004), coma (RR: 23.9, 95%CI:2.85–200.62, p = 0.004), WFNS grade 5 (RR: 18.2, 95%CI:3.7–92.3, p < 0.001), and hospital length ≤ 7 days (RR: 13.5, 95%CI:4.28–42.56, p < 0.001). Conclusion: Mortality and disability of sSAH are still high in our setting. Further studies with prospective follow up of patients are needed to determine the long-term outcome of these patients.